Pediatric Emergency Department Visits Related to Home Accident in the Era of COVID-19 Pandemic - Anıl Er; Berna Kahraman Çetin; Emel Ulusoy; Fatma Akgül; İlker Günay; Hurşit Apa (Galenos Yayinevi, 2023)
Introduction:The Coronavirus disease-2019 pandemic has been caused several physical, mental and psychosocial problems alongside being a respiratory system infection. During pandemic, children were forced to stay at home as a preventative measure. Thus, we aimed to assess the number and characteristics of home accident-related visits in a pediatric emergency department during the pandemic.Methods:This cross-sectional study included all children aged under 18 years who admitted with home accident in two curfew periods and the corresponding periods of previous year. Demographic and clinical data was consisted of age, gender, admission time, time elapsed between accident and pediatric emergency department admission, type of home accident, medical and surgical interventions, length of stay in pediatric emergency department, hospitalization, or intensive care unit admission and mortality. The data of curfew periods was compared with its control periods by using Mann- Whitney U test, t-test or chi-square. The statistical significance was defined as p≤0.05.Results:We enrolled 744 patients. There was no significant difference in age, gender, time elapsed from the accident, ratio of hospitalization between curfew and control periods. The proportions of home accidents among all admissions were higher in two curfew periods (p=0.001 and p<0.001). The ratio of poisoning and foreign body ingestions was increased during both two curfew periods (0.7% vs. 0.3%, p=0.001 and 0.7% vs. 0.1%, p<0.001 for poisoning; 0.4% vs. 0.1%, p<0.001 and 0.8% vs. 0.1%, p<0.001 for foreign body ingestion) and the ratio of trauma was increased in the curfew-2 period (1.2% vs. 0.3%, p<0.001).Conclusion:We suggested a higher ratio of home accidents especially poisoning and foreign body ingestions in curfew period. Thus, in case of global disasters such as pandemic the authorities should improve preventative and healthcare strategies to establish a safe environment for children and adolescents.